A Magnesium Transporter OsMGT1 Plays a Critical Role in Salt Tolerance in Rice. Issue 3 (9th May 2017) - Chen, Zhi Chang; Yamaji, Naoki; Horie, Tomoaki; Che, Jing; Li, Jian; An, Gynheung; Ma, Jian Feng
Abstract : Magnesium transported by OsMGT1 in rice roots is required for enhancing transport activity of OsHKT1;5, which confers salt tolerance through retrieval of Na from xylem vessels. Abstract: Salt stress is one of the major factors limiting rice ( Oryza sativa ) production globally. Although several transporters involved in salt tolerance have been identified in rice, the mechanisms regulating their transport activity are still poorly understood. Here, we show evidence that a rice Mg transporter OsMGT1 is required for salt tolerance probably by regulating transport activity of OsHKT1;5, a key transporter for the removal of Na + from the xylem sap at the root mature zone. Knockout of OsMGT1 did not affect total Na uptake, but increased Na concentration in the shoots and xylem sap, resulting in a significant increase in salt sensitivity at low external Mg 2+ concentration (20–200 μm ). However, such differences were abolished at a higher Mg 2+ concentration (2 mm ), although the total Na uptake was not altered. OsMGT1 was expressed in both the roots and shoots, but only that in the roots was moderately up-regulated by salt stress. Spatial expression analysis revealed that OsMGT1 was expressed in all root cells of the root tips but was highly expressed in the pericycle of root mature zone. OsMGT1 was also expressed in the phloem region of basal node, leaf blade, and sheath. When expressed in Xenopus laevis oocytes, the transport activity of OsHKT1;5 was enhanced by elevating external Mg 2+ concentration. Furthermore, knockout of OsHKT1;5 in osmgt1 mutant background did not further increase its salt sensitivity. Taken together, our results suggest that Mg 2+ transported by OsMGT1 in the root mature zone is required for enhancing OsHKT1;5 activity, thereby restricting Na accumulation to the shoots.